The Plasma Level of Interleukin-1β Can Be a Biomarker of Angiopathy in Systemic Chronic Active Epstein–Barr Virus Infection - Ohashi, Ayaka; Uemura, Yu; Yoshimori, Mayumi; Wada, Naomi; Imadome, Ken-Ichi; Yudo, Kazuo; Koyama, Takatoshi; Shimizu, Norio; Nishio, Miwako; Arai, Ayako (Frontiers in Microbiology, 2022)
Systemic chronic active Epstein-Barr virus infection (sCAEBV) is an EBV-positive T-or NK-cell neoplasm revealing persistent systemic inflammation. 25% of sCAEBV patients accompany angiopathy. It is crucial to clarify the mechanisms of angiopathy development in sCAEBV because angiopathy is one of the main causes of death. Interleukin-1β (IL-1β) is reported to be involved in angiopathy onset. We investigated if IL-1β plays a role as the inducer of angiopathy of sCAEBV. We detected elevated IL-1β levels in 4 out of 17 sCAEBV patient’s plasma. Interestingly, 3 out of the 4 had clinically associated angiopathy. None of the other patients with undetectable level of IL-1β had angiopathy. In all patients with high plasma levels of IL-1β and vascular lesions, EBV-infected cells were CD4-positive T cells. In one patient with high plasma IL-1β, the level of IL-1β mRNA of the monocytes was 17.2 times higher than the level of the same patient’s EBV-infected cells in peripheral blood. In Ea.hy926 cells, which are the models of vascular endothelial cells, IL-1β inhibited the proliferation and induced the surface coagulation activity. IL-1β is a potent biomarker and a potent therapeutic target to treat sCAEBV accompanying angiopathy.